Clinician Experiences in Treatment Decision-Making for Patients with Spinal Metastases: A Qualitative Study. (6th January 2021) - Barton, Lauren B.; Arant, Kaetlyn R.; Blucher, Justin A.; Sarno, Danielle L.; Redmond, Kristin J.; Balboni, Tracy A.; Colman, Matthew; Goodwin, C. Rory; Laufer, Ilya; Placide, Rick; Shin, John H.; Sciubba, Daniel M.; et al.
Abstract : Background: Effective management of metastatic disease requires multidisciplinary input and entails high risk of disease-related and treatment-related morbidity and mortality. The factors that influence clinician decision-making around spinal metastases are not well understood. We conducted a qualitative study that included a multidisciplinary cohort of physicians to evaluate the decision-making process for treatment of spinal metastases from the clinician's perspective. Methods: We recruited operative and nonoperative clinicians, including orthopaedic spine surgeons, neurosurgeons, radiation oncologists, and physiatrists, from across North America to participate in either a focus group or a semistructured interview. All interviews were audiorecorded and transcribed verbatim. We then performed a thematic analysis using all of the available transcript data. Investigators sequentially coded transcripts and identified recurring themes that encompass overarching patterns in the data and directly bear on the guiding study question. This was followed by the development of a thematic map that visually portrays the themes, the subthemes, and their interrelatedness, as well as their influence on treatment decision-making. Results: The thematic analysis revealed that numerous factors influence provider-based decision-making for patients with spinal metastases, including clinical elements of the disease process, treatment guidelines, patient preferences, and the dynamics of the multidisciplinary care team. The most prominent feature that resonated across all of the interviews was the importance of multidisciplinary care and the necessity of cohesion among a team of diverse health-care providers. Respondents emphasized aspects of care-team dynamics, including effective communication and intimate knowledge of team-member preferences, as necessary for the development of appropriate treatment strategies. Participants maintained that the primary role in decision-making should remain with the patient. Conclusions: Numerous factors influence provider-based decision-making for patients with spinal metastases, including multidisciplinary team dynamics, business pressure, and clinician experience. Participants maintained a focus on shared decision-making with patients, which contrasts with patient preferences to defer decisions to the physician, as described in prior work. Clinical Relevance: The results of this thematic analysis document the numerous factors that influence provider-based decision-making for patients with spinal metastases. Our results indicate that provider decisions regarding treatment are influenced by a combination of clinical characteristics, perceptions of patient quality of life, and the patient's preferences for care.